2014
DOI: 10.1002/ajmg.b.32238
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation status of human brain derived neurotrophis factor gene could be useful as biomarker of depression

Abstract: Brain-derived neurotrophic factor (BDNF) is involved in the survival, development, and synaptic plasticity of neurons. BDNF is believed to be associated with the pathophysiology of psychiatric disorders. Several studies have suggested the relevance of DNA methylation in its promoter region with depression. Here, we report different methylation statuses in groups with different depressive scores or undergoing different levels of job-stress. DNA samples were extracted from the saliva of 774 Japanese workers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 47 publications
(61 reference statements)
1
39
0
Order By: Relevance
“…Increased DNA methylation at Bdnf gene promoter was observed in DNA from peripheral blood mononuclear cells of patients affected with major Page 10 of 20 A c c e p t e d M a n u s c r i p t 9 depression as compared to control subjects [34,35]. However, lower methylation levels in saliva DNA were associated with symptoms of depression in Japanese workers [36]. Bdnf promoter hypermethylation in blood DNA was found in bipolar disorder type II patients in comparison with controls and with bipolar disorder type I cases [37].…”
Section: Discussionmentioning
confidence: 99%
“…Increased DNA methylation at Bdnf gene promoter was observed in DNA from peripheral blood mononuclear cells of patients affected with major Page 10 of 20 A c c e p t e d M a n u s c r i p t 9 depression as compared to control subjects [34,35]. However, lower methylation levels in saliva DNA were associated with symptoms of depression in Japanese workers [36]. Bdnf promoter hypermethylation in blood DNA was found in bipolar disorder type II patients in comparison with controls and with bipolar disorder type I cases [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the DNA methylation profiles of the CpG island of the BDNF gene have shown that this gene could be useful as a biomarker of major depression [13,28]. The BDNF gene has been implicated as a susceptible locus for addiction to multiple drugs of abuse, such as alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…J-HOPE is a national level, large-scale occupational cohort study on social class and health in Japanese workers involving more than ten thousand employees representing a number of different industries [16][17][18][19]; the study was initiated in 2009 and designed as a 5-year follow-up survey. For the current study, workers of a major manufacturing company with offices spread all over Japan were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…We previously investigated human mental health and its contributing factors in a large occupational cohort study (Japanese Study of Health, Occupation, and Psychosocial Factors Related Equity; J-HOPE) [16][17][18][19]. Since there is little evidence about epigenetic changes in the human TH gene in response to stress, we aimed to elucidate the DNA methylation state of the human TH gene in a non-invasive manner by referring to occupational cohort data that includes information on both validated stress markers [20][21][22] and a depression score [23,24].…”
Section: Introductionmentioning
confidence: 99%